Intellectual property challenges for the roads of innovation in Brazil - Cleiton Rodrigues de Vasconcelos; Daniel Pereira da Silva (Innovation & Management Review, 2019)
Purpose - This paper aims to present reflections and points of interest on the performance of Brazil and highlight the advances and challenges in relation to the intellectual property (IP) system; the authors highlight some scientific, economic and technological indicators on the main IP objects registered in the National Industrial Property of Brazil (INPI). Design/methodology/approach - A structured literature reviews the main indicators of IP of Brazil (2013-2017), related to the scientific and economic factors more evidenced in the global scenario, with emphasis on the investment of national GDP in R&D activities, the allocation of resources from the government sector and private initiative, as in other emerging economies, such as the BRICS. Findings - Despite Brazil's progressive efforts to achieve greater efficiency in the public IP management system, GDP investment in R&D activities for 2019 is still below the OECD average of 2.3 per cent, and the IP indicators in the areas of patent registration, industrial designs and technology contracts have been declining. Research limitations/implications - Because of the difference between the laws of the countries on IP rights, the more incisive comparison could not be established among the emerging economies, highlighting the need for a standardization between the different international legislations. Originality/value - In the scientific field, this paper allows understanding the performance of the Brazilian IP system, and the categories that require greater investments, strengthen the IP culture and stimulate integration between the international IP systems, as it is a recurrent discussion in different research studies. Originally, the paper brought together economic and scientific indicators going beyond the traditional approach that deals with IP only restricting to the quantitative of patents.
Keywords: Q43; C52; 650; Indicators; Intellectual property management; Performance Brazil